Skills Gap Challenge: How Apprenticeship Programs Address Skill Building and Educational Advancement (Journal of Organizational Psychology, 2020)
The job market reflects a complex set of employability issues when higher education, technical training and job fill rates are considered (Chaitanya, 2018; Moore & Morton, 2017). As a result, skills gap or job readiness issues have emerged (Moore & Morton, 2017), with a detrimental impact on employers and organizations (e.g., lack of productivity, performance, etc.) as well as employees (e.g., turnover, poor person- job fit, etc.). To help fill the void created by this mismatch, organizations are investing in apprenticeship programs. While the benefits of these programs are significant, opportunities exist to maximize overall apprentice performance and success.
Keywords: Organizational Psychology; apprenticeship programs, skills gap, realistic job preview, person-environment fit, person-job fit, person-organization fit